Demands and Challenges in Higher Education Today - Pante-Salas, Giovanna Gladys; Quiñones-Colchado, Elva Rosa; Cuya-Candela, Edita Rumualda; López-Sánchez, Milena; Choque , Pilar Maria, Gamarra; Alvarez, Carlos Alberto Villafuerte (Journal of Ecohumanism, 2025)
The changing situation of society has brought many challenges and demands to Higher Education (HE), which considers many aspects such as: the impact of the Covid-19 pandemic, the SDGs, the 2030 agenda, the use of AI, among others, therefore this article aims to analyze the demands and challenges of higher education today and to know which aspects are unknown or controversial, thus a literature review was conducted on higher education considering research from different countries around the world, within the main results of the analysis of 30 scientific articles, it was found that HE, is multidimensional since it encompasses different aspects such as social, environmental and economic aspects, and hence it presents different demands and challenges for which the implementation of different strategies is proposed.